2015
DOI: 10.1136/bmjopen-2014-007443
|View full text |Cite
|
Sign up to set email alerts
|

Does a quality management system improve quality in primary care practices in Switzerland? A longitudinal study

Abstract: ObjectivesTo examine the effectiveness of the quality management programme—European Practice Assessment—in primary care in Switzerland.DesignLongitudinal study with three points of measurement.SettingPrimary care practices in Switzerland.ParticipantsIn total, 45 of 91 primary care practices completed European Practice Assessment three times.OutcomesThe interval between each assessment was around 36 months. A variance analyses for repeated measurements were performed for all 129 quality indicators from the doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 19 publications
(26 reference statements)
2
18
0
2
Order By: Relevance
“…As a motivational aspect practices get a certificate if they successfully complete EPA. Further information about EPA in Switzerland is given in Goetz et al 20…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a motivational aspect practices get a certificate if they successfully complete EPA. Further information about EPA in Switzerland is given in Goetz et al 20…”
Section: Methodsmentioning
confidence: 99%
“…21 Data were collected from 91 practices, which had used the EPA methodology and published elsewhere. 20 190 primary care physicians worked in these practices. Not all physicians enrolled into EPA participated in the job satisfaction survey.…”
Section: Design and Participantsmentioning
confidence: 99%
“…In general practice, there is a pronounced lack of empirical research on the implementation and impact of accreditation [3] and the sparse evidence on impact is inconclusive. Two before-after studies from Germany and Switzerland reported improvements in practice management from participation in voluntary accreditation under the European Practice Assessment program [7, 8]. However, these studies had important methodological limitations and did not include clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 15 These factors have led to poor accessibility and high medical costs for people seeking medical care in hospitals. 16 …”
Section: Introductionmentioning
confidence: 99%